Rapid improvement of obsessive-compulsive disorder associated with schizophrenia with cariprazine add-on in a subject under paliperidone long-acting injection: a case report. (March 2020) - De Berardis, Domenico; Vellante, Federica; Fornaro, Michele; Orsolini, Laura; Valchera, Alessandro; Baroni, Gaia; Kim, Yong-Ku; Martinotti, Giovanni; Di Giannantonio, Massimo
Abstract : Obsessive-compulsive disorder is often associated with schizophrenia and may represent a significant challenge in the treatment as this comorbidity may not respond properly to antipsychotic medication and usually require a pharmacological and psychotherapeutic add-on. In the present case report, we present the case of a 26-year-old male blue-collar subject who developed obsessive-compulsive disorder after a year of complete remission of schizophrenia symptoms under paliperidone long-acting injection that rapidly resolved after low-dosage cariprazine add-on. No adverse effects were reported due to cariprazine- paliperidone long-acting injection combination.